DETERMINANT MODEL OF COMPANY VALUE IN THE PROPERTY AND INFRASTRUCTURE SECTOR - Zurriah, Rezki; Ammy, Baihaqi; Parlindungan, Ronni (CV. Radja Publika, 2021)
The purpose of this study is to find out and test the effect of good corporate governance, company size, dividend policy, debt policy and profitability on the value of companies in the property and infrastructure sectors in 2008-2017 listed securities in Indonesia. This study is a causal study using secondary data. The population in the study amounted to 63 property and infrastructure companies registered with the IDX for the period 2008-2017. The sampling technique used in this study is purposive sampling where the entire population of 35 companies is used as data in this study. The analysis tool used in this study used regression analysis of panel data.